Up‐regulation of the chemo‐attractive receptor ChemR23 and occurrence of apoptosis in human chondrocytes isolated from fractured calcaneal osteochondral fragments. Issue 6 (1st April 2014) - Sena, Paola; Manfredini, Giuseppe; Benincasa, Marta; Mariani, Francesco; Smargiassi, Alberto; Catani, Fabio; Palumbo, Carla
Abstract To study the expression level of a panel of pro/anti‐apoptotic factors and inflammation‐related receptors in chondral fragments from patients undergoing surgical treatment for intra‐articular calcaneal fractures, cartilage fragments were retrieved from calcaneal fractures of 20 patients subjected to surgical treatment. Primary cultures were performed using chondral fragments from fractured and control patients. Chondrocyte cultures from each patient of the fractured and control groups were subjected to immunofluorescence staining and quantitatively analyzed under confocal microscopy. Proteins extracted from the cultured chondrocytes taken from the fractured and control groups were processed for Western blot experiments and densitometric analysis. The percentage of apoptotic cells was determined using the cleaved PARP‐1 antibody. The proportion of labelled cells was 35% for fractured specimens, compared with 7% for control samples. Quantification of caspase‐3 active and Bcl‐2 proteins in chondrocyte cultures showed a significant increase of the apoptotic process in fractured specimens compared with control ones. Fractured chondrocytes were positively stained for ChemR23 with statistically significant differences with respect to control samples. Densitometric evaluation of the immunoreactive bands confirmed these observations. Human articular chondrocytes obtained from patients with intra‐articular calcaneal fractures express higher levels of pivotal pro‐apoptotic factors, and of the chemo‐attractive receptor ChemR23, compared with control cultures. On the basis of these observations, the authors hypothesize that consistent prolonged chondrocyte death, associated with the persistence of high levels of pro‐inflammatory factors, could enhance the deterioration of cartilage tissue with consequent development of post‐traumatic arthritis following intra‐articular bone fracture.